2019
DOI: 10.3389/fevo.2019.00066
|View full text |Cite
|
Sign up to set email alerts
|

Squirrels Do the Math: Flight Trajectories in Eastern Gray Squirrels (Sciurus carolinensis)

Abstract: Animals are under strong selective pressures to make correct decisions when attempting to escape an approaching predator, and not surprisingly many studies have shown that animals adjust their flight initiation behavior in response to risk. However, we have a poor understanding of animals' capability to select an appropriate flight trajectory. We investigated whether eastern gray squirrels would adjust their flight trajectory based on the relative locations of the squirrel, the approaching threat, and potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…Our results demonstrated that when compared with other variables typically reported to explain variation in FID, such as alert distance and level of human disturbance, Φ explained significant variation in FID. Our results are consistent with Kramer and Bonenfant’s (1997) original findings, as well as those in Cooper Jr.’s (2016) race for life model, and recent empirical findings reported by Eason et al (2019) . In all cases, as Φ decreased, FID decreased.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results demonstrated that when compared with other variables typically reported to explain variation in FID, such as alert distance and level of human disturbance, Φ explained significant variation in FID. Our results are consistent with Kramer and Bonenfant’s (1997) original findings, as well as those in Cooper Jr.’s (2016) race for life model, and recent empirical findings reported by Eason et al (2019) . In all cases, as Φ decreased, FID decreased.…”
Section: Discussionsupporting
confidence: 93%
“…However, animals may not make as fine distinctions in angle when making escape decisions, and may use coarser assessments of predator risk due to orientation. Therefore, we parameterized a series of GLMs in which we binned our data into different categories comprising different angles ( Figure 4 ) which were based on the predictions of the models of Kramer and Bonenfant (1997) , and Cooper (2016) and empirical results reported by Eason et al (2019) . Using AIC to compare model fits, we then assessed which angle categorization scheme most effectively explained variation in our data.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…FID is an outstanding metric for measuring an individual's fearfulness under certain conditions [26], and flight response is also studied to recognize the areas where the species are not influenced by humans [27]. This index has been studied in several species from different taxa, particularly in birds [28], fishes or lizards [7] [29] [30], ungulates and small mammals [23] [31] [32] [33]. However, no study has been conducted so far on the cape hare, a species that occurs in a heavily hunted landscape in the Karakorum Range.…”
Section: Introductionmentioning
confidence: 99%
“…Next, we tested escape route selection in four different arenas where the length of the left arm was progressively increased while keeping constant the initial angle between each path and the threat platform (arenas 1-4, Figure 1D). In this experiment the relative value of the left hand-side path decreases between arenas 1 and 4 as mice should in principle escape along the shortest path to minimize exposure to danger [10][11][12]. The differences in geodesic distance (path length) between the threat and shelter platforms translated not only into differences in distance travelled but also into time taken to traverse each path during escape (Figure S1C, D).…”
Section: Escape Route Choice Is Determined By Path Distance and Angle To Sheltermentioning
confidence: 93%